Bridging the rural‐urban divide: An implementation plan for leveraging technology and artificial intelligence to improve health and economic outcomes in rural America - Weeks, Bill, Justin Spelhaug; Weinstein, James; Lavista Ferres, Juan M. (The Journal of Rural Health, 2024)
Rural residents and the rural hospitals that serve them are increasingly under advantaged compared to their urban counterparts. We propose a phased technological transformation process that can improve national security, improve productivity and financial sustainability, achieve the quadruple aim, improve the local economic environment, and provide local access to technology, skilling, educational, and cultural experiences in rural settings. Such an initiative could stabilize rural economic environments and potentially reverse longstanding rural-urban health disparities.